Analysis and Characterization of Herpes Simplex Virus After Its Persistance in a Lymphoblastoid Cell Line for 15 Months - Roumillat, L. F. (1980)
Infection of a human lymphoblastoid cell line (F-365 line containing Epstein-Barr viral capsid antigen, derived from an individual without overt signs of lymphoma, infectious mononucleosis, or leukemia) with herpes simplex virus (HSV), maintained and observed for 15 months, was characterized by the continuous production of infectious extracellular virus. By the 5th day postinfection 75% of the cells produced HSV antigen as detected by fluorescent antibody, and by the 10th day 90% did so; production continued through the 15th month. Only 11% of single isolated cells produced detectable infectious virus. HSV produced after the 3rd month formed smaller plaque in monolayer cell culture than did the parental virus. No antigenic or polypeptide change in the HSV was detected by crossed immunoelectrophoresis and sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis over the 15-month cultivation in F-365 cells. Cell susceptibility and HSV virulence did not appear to change. The HSV-lymphoblastoid cell culture provided a useful model in which to study long-term virus-cell interactions.